Pengaruh Leverage, Pertumbuhan Aset, dan Pertumbuhan Penjualan Terhadap Profitabilitas pada Perusahaan Holding Company (Studi pada Perusahaan yang Terdaftar di BEI Periode 2017 – 2021) - Lina Karlina; Nugraha Nugraha; Harpa Sugiharti (Jurnal Pendidikan Akuntansi & Keuangan, 2023)
This study aims to determine the effect of leverage, asset growth, and sales growth on profitability in holding companies listed on the IDX for the 2017-2021 period. The independent variables in this study consist of leverage (DAR), asset growth (AG), and sales growth (SG). While the dependent variable in this study is profitability (ROA). The method used in this research is descriptive verification method with a quantitative approach. The data collection technique used is a documentation technique that originates from the annual report and annual financial report of the holding company obtained through the IDX website. The sampling technique was purposive sampling with a sample of 43 holding company companies for 5 years of observation from 2017-2021, totaling 215 companies. The results of the regression significance test (F test) indicate that the regression model can be used to draw conclusions. As for the value of the t test results indicate that leverage has a negative effect on profitability, asset growth has a positive effect on profitability, and sales growth has a positive effect on profitability.